2019
DOI: 10.3390/antiox8120619
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Influences between Nitric Oxide and Paraoxonase 1

Abstract: One of the best consolidated paradigms in vascular pharmacology is that an uncontrolled excess of oxidizing chemical species causes tissue damage and loss of function in the endothelial and subendothelial layers. The fact that high-density lipoproteins play an important role in preventing such an imbalance is integrated into that concept, for which the expression and activity of paraoxonases is certainly crucial. The term paraoxonase (aryldialkyl phosphatase, EC 3.1.8.1) encompasses at least three distinct iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 86 publications
0
14
0
Order By: Relevance
“…Some authors have concluded that the principal biochemical mechanisms involved in inducing OS in obesity are hyperleptinaemia, low antioxidant defences and chronic inflammation 28‐31 . Therefore, obesity is not only characterized by an OS state, but it is also defined as a low‐grade inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have concluded that the principal biochemical mechanisms involved in inducing OS in obesity are hyperleptinaemia, low antioxidant defences and chronic inflammation 28‐31 . Therefore, obesity is not only characterized by an OS state, but it is also defined as a low‐grade inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have concluded that the principal biochemical mechanisms involved in inducing OS in obesity are hyperleptinaemia, low antioxidant defences and chronic inflammation. [28][29][30][31] Therefore, obesity is not only characterized by an OS state, but it is also defined as a low-grade inflammatory disease. In agreement with this, together with the low values of the antioxidant enzymes PON1 and CAT, we found leptin values 4 times higher in morbidly obese patients than 1 year after BS, in addition to high CRP levels that were 5 times higher before BS.…”
Section: F I G U R Ementioning
confidence: 99%
“…Paraoxonase 1 (PON1) is an accessory protein of HDL which, in intimate and mutual coordination with Apolipoprotein A1 (APO A1), contributes to the lipoprotein functionality [ 14 , 15 , 16 ]. In particular, it has been widely demonstrated that PON1 protects HDL, low-density lipoprotein (LDL), endothelial cells, and intimal macrophages from oxidative insult [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that PON1 activity is modulated only by resistin, among other cytokines and adipokines evaluated (IL-6, IL-8, TNF-α, leptin, adiponectin) (40). Furthermore, it is currently accepted that high levels of peroxynitrite can 0lead to modification of PON1 activity (41). This parameter could not be evaluated in our study.…”
Section: Discussionmentioning
confidence: 76%